Handling of medical malapractice criminal in criminal Law policies - Muhammad Yusuf (Faculty of Law, Universitas Pekalongan, 2022)
The study aims to determine (1) the applicable current criminal law policy concerning the medical malpractice. (2) the future criminal law concerning the medical malpractice,and (3) the mechanism for medical malpractice settlement. The study uses normative juridical approach that is bibliographical review to obtain the secondary data. The study reveals that: 1. The settlement of medical malpractice in the current positive law is in the articles : 267, 322, 344, 345, 349, 359, 360, 386, and 531 of the Criminal Code, and Articles : 190,192,193,194,195, and 196 of the Law No. 36 of 2009 of Health, articles 75,76,77,78,79, and 80; Law No. 29 of 2004;Indonesian positive law of either Penal Code, Law No. 36 of 2009 on Health, Law No. 29 of 2004 on Medical Practice Law,or the post-verdict of Constitutional Court has not specifically covered malpractice. 2. The future criminal law policy in the settlement of medical malpractice has to be driven from the positive law, particularly Articles 575,576,578,589,592, and 593 of Penal Code draft of 2008. 3. The mechanism of malpractice case settlement for both criminal and civil law suit between doctors and hospitals against the patients and the family or their representatives can be done either in litigation (in court) or in non-litigation (outside court)